AI Integration for Business Sustainability For a Resilient Future - Al Qamashoui, Aziza; Al Baimani, Nasser (Contributions to Environmental Sciences & Innovative Business Technology, 2025)
XI, 434 p. 52 illus., 46 illus. in color.